Dose-Response Comparison of RRR-alpha-Tocopherol and All-Racemic alpha-Tocopherol on LDL Oxidation - Devaraj, S.; Adams-Huet, B.; Fuller, C.J.; Jialal, I. (Arteriosclerosis, thrombosis, and vascular biology, 1997)
Much data have accrued in support of the concept that oxidation of LDL is a key early step in atherogenesis. The most consistent data with respect to micronutrient antioxidants and atherosclerosis appear to relate to alpha-tocopherol (AT), the predominant lipid-soluble antioxidant in LDL. There are scant data on the direct comparison of RRR-AT and all-racemic (rac)-AT on LDL oxidizability. Hence, the aim of the present study was to examine the relative effects of RRR-AT and all-rac-AT on plasma antioxidant levels and LDL oxidation in healthy persons in a dose-response study. The effect of RRR-AT and all-rac-AT at doses of 100, 200, 400, and 800 IU/d on plasma and LDL AT levels and LDL oxidation was tested in a randomized, placebo-controlled study of 79 healthy subjects. Copper-catalyzed oxidation of LDL was monitored by measuring the formation of conjugated dienes and lipid peroxides over an 8-hour time course at baseline and again after 8 weeks. Plasma AT, lipid-standardized AT, and LDL AT levels rose in a dose-dependent fashion in both the RRR-AT and all-rac-AT groups compared with baseline. There were no significant differences in plasma, lipid-standardized, and LDL AT levels between RRR-AT and all-rac-AT supplementation at any dose comparison. The lag phases of oxidation were significantly prolonged with doses >or= to 400 IU/d of RRR-AT and all-rac-AT, as measured by conjugated-dienes assay and at 400 IU/d of RRR-AT and 800 IU/d of both forms of AT by lipid peroxide assay. Again, there were no significant differences in the lag phase of oxidation at each dose for RRR-AT when compared with all-rac-AT. Also, there were no significant differences in LDL oxidation after in vitro enrichment of LDL with RRR-AT and all-rac-AT. Thus, supplementation with either RRR-AT or all-rac-AT resulted in similar increases in plasma and LDL AT levels at equivalent IU doses, and the degree of protection against copper-catalyzed LDL oxidation was only evident at doses >or= to 400 IU/d for both forms. (Arterioscler Thromb Vasc Biol. 1997;17:2273-2279.)